Knowledge, Attitude and Skills of Oral Health Care Professionals towards Cancer Treatment-induced Oral Mucositis. - Swapnil Mohod, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background and objectives: More than 90% of patients with head and neck malignancies develop cancer treatment-induced oral mucositis CT-IOM. It is commonly referred to stomatitis. It is a common, dose-limiting, and potentially life-threatening side effect of radiation or chemotherapy. The present study aimed to assess the knowledge, attitude, and skills of oral health care professionals working in different settings regarding the treatment and care of CT-IOM. Material and methods: This study used a questionnaire with 20 questions that was circulated to oral health care providers using Google Forms. The questionnaire collected data regarding the knowledge, attitude, and skills of oral health care professionals of CT-IOM using multiple answers questions and a Likert scale. The obtained information from the responders was statistically analyzed. Statistical analysis was done using SPSS software. Results: The study was conducted to compare the knowledge, attitude and skills among three groups of private practitioners, dental hospital and general hospitals. Among all the oral healthcare professionals, the responders working in the dental hospital setup are more aware than the private practitioners and the ones working in general hospitals of palliative care in CT-IOM Conclusion: The study concluded by stating that oral healthcare professionals need to be sensitized regarding palliative care and knowledge of CT-IOM.